Fatores relacionados ao início planejado da diálise entre os pacientes diabéticos do município de Belo Horizonte (MG, Brasil) - Eline Rezende de Morais Peixoto (2012)
Diabetes mellitus is the second leading cause of End Stage Renal Disease in Brazil, accounting for about 30% of patients on dialysis programs. There is evidence that a care predialysis poor results in unplanned start of renal replacement therapy. The aim of this thesis was to analyze the factors associated with planned start of dialysis in diabetic patients who started treatment within 12 units providing dialysis, attending the National Health System in the city of Belo Horizonte. It is cross-sectional study of 250 diabetic patients who started dialysis between Jan/2006 and Dec/2007. We considered patients with planned start of dialysis who started hemodialysis with an arteriovenous fistula or peritoneal dialysis. We investigated sociodemographic, clinical and utilization of health services through semi-structured interviews. For multivariate analysis, we used Poisson regression. Of the 250 diabetic patients, 239 patients (95.2%) started dialysis and hemodialysis modality in 12 (4.8%) on peritoneal dialysis, with a total of 70% started dialysis in an unplanned manner. Among those who started on hemodialysis, 63 (26.5%) used as arteriovenous fistula access. Most patients were male (54.8%) with a mean age of 58.97 years (SD = 13.01 years), with up to eight years of education (68.4%), belonging to economy class C , D and E (66.4%) and did not have health insurance (56.0%). A total of 83.6% of patients with nephrologist consulted before the start of dialysis, while 67% of them were referred to query over 12 months before the initiation of treatment. Report having hypertension, attend health center, have the first appointment with a nephrologist paid by SUS and had option of choice for the treatment of chronic kidney disease-related factors were terminal planned start of dialysis. It is observed that the beginning of unplanned dialysis is common in the city of Belo Horizonte and occurs regardless of the time of referral to the nephrologist. Efforts are needed to articulate the network of existing services and their organization into a model of care focused on key population groups at risk for chronic kidney disease, besides the improvement of preventive and curative health care activities through an appropriate preparation of the healthcare team who deal daily with these patients.